Radiation studies performed on the High Luminosity ATLAS TileCal link Daughterboard. (1st April 2023) - Valdes Santurio, E.; Silverstein, S.; Bohm, C.; Motzkau, H.; Clement, C.; Dunne, K.; Lee, S.; ,
Abstract: The new electronics of the ATLAS Tile Calorimeter for the HL-LHC interfaces the on-detector and off-detector electronics by means of a Daughterboard. The Daughterboard is positioned on-detector featuring commercial SFPs+, CERN GBTx ASICs, ProASIC FPGAs and Kintex Ultrascale FPGAs. The design minimizes single points of failure and mitigates radiation damage by means of a double redundant scheme, Triple Mode Redundancy, Xilinx Soft Error Mitigation IP, CRC/FEC for link data transfer, and SEL protection circuitry. We present an updated summary of the TID, NIEL and SEE qualification tests, and performance studies of the Daughterboard revision 6 design.